Dating possibilities for the South African hominid sites - Vogel, J. C. (Bernard Price Institute for Palaeontological Research, 1980)
A brief description is given of dating methods which may in future prove to be applicable to the calcified ossiferous cave deposits of the early hominid sites in the Transvaal. Potentially the techniques based on amino acid racemisation, uranium series disequilibrium and radiation damage could provide dates for at least the upper members of the cave formations. The results would, however, have. to be calibrated in the younger time-range by radiocarbon dating of parallel samples.
Main article
Keywords: dating; hominid sites; South Africa